2020
DOI: 10.1186/s12909-020-1935-x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional and cross-sectional study on empathy in Chinese medical students: differences by student cadre or not, future career preference, and father’s education status

Abstract: Background: The aims of this study were to examine the factor structure of the Chinese version of the Jefferson Scale of Empathy for medical students (JSE-S) and investigate differences in empathy scores among Chinese medical students according to gender, student cadre or not, future career preference, and parents' education. Methods: Medical students from three universities completed an online questionnaire containing the JSE-S. Exploratory factor analysis was conducted to determine the factor structure, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
5
3
Order By: Relevance
“…This finding is consistent with the vast majority of prior studies. Many studies conducted across various cultures reported statistically significant differences in overall empathy scores between male and female students and confirmed that female medical students are more empathetic than their male counterparts [ 10 , 14 , 15 , 16 , 17 , 25 , 29 , 33 , 37 , 55 , 57 , 58 , 60 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 76 , 83 , 84 , 89 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. As mentioned above, this discrepancy changes across the academic years.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This finding is consistent with the vast majority of prior studies. Many studies conducted across various cultures reported statistically significant differences in overall empathy scores between male and female students and confirmed that female medical students are more empathetic than their male counterparts [ 10 , 14 , 15 , 16 , 17 , 25 , 29 , 33 , 37 , 55 , 57 , 58 , 60 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 76 , 83 , 84 , 89 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. As mentioned above, this discrepancy changes across the academic years.…”
Section: Discussionmentioning
confidence: 94%
“…Archer and Turner (in South Africa) found that “The mean JSE was 109.98 (SD = 12.54), which is lower than most internationally reported scores” [ 96 ]. Yi et al (in China) found that “The total mean was 104.66 (SD = 13.09), and scores ranged from 39 to 137” [ 97 ]. Shaheen et al (in Pakistan) found that “overall mean empathy level was 90.63 ± 11.55” [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, most studies found that medical students who preferred a people-oriented specialty had significantly higher empathy scores [ 9 , 13 , 20 ]. Besides, age, parent educational level, race and ethnicity and caring behaviors also were predictors of medical students’ empathy [ 22 , 23 ]. The empathy of medical students in China has been investigated by some studies already [ 22 , 24 , 25 ], but depths of these studies were not enough, and the sample sizes were limited.…”
Section: Introductionmentioning
confidence: 99%